EFFECTS OF A WEB-BASED NEED-SUPPORTIVE INTERVENTION PROGRAM ON PHYSICAL EDUCATION TEACHER OUTCOMES (Kinesiology, 2025)
Interventions aimed at enhancing need-supportive behaviours have predominantly focused on assessing their effects on student outcomes, thereby placing comparatively less emphasis on gains experienced by teachers. This study investigated whether a web-based need-supportive intervention programme for physical education (PE) teachers would also provide significant gains in enhancing PE teachers need-supportive behaviours, psychological need satisfaction, intrinsic motivation to teach, teaching efficacy and reducing their controlling behaviours. Participants were 74 PE teachers (54 women). Their average age was 46.04 years (SD = 12.64), and they had an average teaching experience of 17.33 years (SD = 13.83). Participants were allocated into experimental and control conditions. PE teachers in the experimental group completed a four-week web-based need-supportive intervention programme. Results demonstrated that the experimental group PE teachers demonstrated significant gains in their autonomy support, competence support and teaching efficacy compared to the control group PE teachers within a one-month follow-up. These results suggest that our web-based need-supportive intervention programme for PE teachers was partially effective to produce gains for PE teachers themselves.Key words: autonomy support, competence support, relatedness support, controlling behaviour, motivation, teaching efficacy